Legal Status of the Voivodship Marshal in the Light of Its Functions - Jacek Sobczak (Barometr Regionalny, 2019)
The legal status of the voivodship marshal is determined by a number of conditions. The most important are functions and powers vested in this authority under the Act on the voivodship government, other laws and provisions of secondary legislation. The analysis of these regulations determines the strong legal position of the voivodship marshal, which allow for including this authority in the category of local government bodies, even though the Constitution and the Act on the voivodship government mention only the voivodship assembly and the voivodship board as local government authorities. The independent, managerial powers in the voivodship board, and in particular the right to issue administrative decisions in individual cases, frame this institution as a monocratic authority. This conclusion allows putting forward a proposal concerning direct election of this authority by the inhabitants of the voivodship.